What Do Adolescents Know About One-Health and Zoonotic Risks? A School-Based Survey in Italy, Austria, Germany, Slovenia, Mauritius, and Japan - Paolo Zucca; Paolo Zucca; Marie-Christin Rossmann; Marie-Christin Rossmann; Mitja Dodic; Yashwantrao Ramma; Toshiya Matsushima; Steven Seet; Susanne Holtze; Alessandro Bremini; Alessandro Bremini; Ingrid Fischinger; et al. (Frontiers Media S.A., 2021)
More than 60% of the 1,700 infectious diseases that affect human come from animals and zoonotic pandemics, after starting from sporadic phenomena limited to rural areas, have become a global emergency. The repeated and frequent zoonotic outbreaks such as the most recent COVID-19 pandemic can be attributed also to human activities. In particular, the creation of enormous intensive domestic animal farms, the indiscriminate use of antibiotics, the destruction of forests, the consumption of the meat of wild animals and the illegal animal trade are all factors causing the insurgence and the transmission of zoonotic diseases from animals to humans. The purpose of this study was to explore the knowledge of the One Health concept including the zoonotic risk potentially derived from illegally traded pet animals and wildlife among adolescents in 6 different countries (Italy, Austria, Slovenia, Germany, Mauritius, and Japan). A representative sample of 656 students was recruited and all participants took an anonymous questionnaire. Data were analyzed by ANOVAs to estimate the prevalence of correct health prevention behaviors and to identify the influential factors for these behaviors. After two theoretical-practical lectures, the same anonymous questionnaire was administered for the second time in order to assess the efficacy of the program. The proportion of students who did not know that many diseases affecting humans come from animals is 28.96% while 32.16% of them did not know what a zoonosis is. The circularity of the One Health concept related to the transmission of diseases from animals to humans and vice-versa is not understood from a large prevalence of the adolescents with 31.40 and 59.91% of wrong responses, respectively. Furthermore, rabies is not considered as a dangerous disease by 23.02% of the adolescents. After two theoretical-practical classroom sessions, the correct answers improved to 21.92% according to the different question. More than a third of the student cohort investigated showed a profound ignorance of the zoonotic risks and a poor understanding of the One Health concept. The authors believe that the teaching of health prevention with a One Health approach and a practical training should be included in every school curriculum.